Efeito da peçonha de Bothrops moojeni sobre formas promastigotas de Leishmania spp - Castilhos, Patrícia de (2008)
In order to develop alternative tools to subdue infectious diseases, several substances have been tested toward treatment of parasitoses, such as Leishmaniasis. For this purpose, snake venoms have been used as future drugs that disrupt the viability of protozoan. In this report, we evaluated the effect of Bothrops moojeni venom and its fractions on viability, protein profile, infectivity and nitric oxide production of Leishmania promastigotes in vitro . Bothrops moojeni venom was fractionated into five protein fractions (E1 to E5) by ion exclusion chromatography and used to treat on L. (L.) amazonensis and L. (V.) braziliensis promastigote forms. The viability of Leishmania promastigotes was evaluated by MTT test and nitric oxide production was detected in supernatants of Leishmania culture. It was observed that E5 fraction strongly inhibited NO production in different concentrations in L. amazonensis, while in L. brasiliensis the NO production was enhance in ever concentration. It was also observed that crude venom of B. moojeni inhibited the viability of the both parasites in a dose dependent manner. However the E5 fraction only inhibited the viability of L. amazonensis. Also a peptide of 64 kDa of L (L.) amazonensis was apparently degraded in other two peptides with 56 and 51 kDa respectively. Moreover, when Leishmania spp was treated with E5 fraction and amphotericin B was not observed degradation of proteins. And after studies with the E5 fraction in DEAE (-) Sephacel, it was realized the exclusion cromatography and was obtained six new fractions (E5G1 and E5G6) and the cellular viability Leishmania (L.) amazonensis was sensitive to E5G1 (≥ 0.156 μg) and E5G5 (≥ 0.313μg). Adicionaly, it was analyzed the effect of Bothrops moojeni venon and the E5 fraction in the lesion progression of BALB/c mice infected with L. amazonensis and during the following period of lesion evolution (six weeks) it was verified that the thickness of the footpads of all infected animals with pre treated parasites did not increase in comparison to the non infected contralateral footpad. Thus, we demonstrated that Bothrops moojeni venom inhibited NO production, altered the protein profile and reduced the viability and infectivity of Leishmania promastigotes in vitro .